2019
DOI: 10.1101/848374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical analysis and optimality of neural systems

Abstract: Normative theories and statistical inference provide complementary approaches for the study of biological systems. A normative theory postulates that organisms have adapted to efficiently solve essential tasks, and proceeds to mathematically work out testable consequences of such optimality; parameters that maximize the hypothesized organismal function can be derived ab initio, without reference to experimental data. In contrast, statistical inference focuses on efficient utilization of data to learn model par… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Later, Teti et al (69) employed sparse coding with lateral inhibition in simulations of neuronal activation in visual cortex. More recently, Młynarski et al (41) presented a probabilistic framework combining normative priors with statistical inference and demonstrated the usefulness of this approach for the analysis of diverse neuroscientific datasets. However, their work was rather conceptual, with the datasets they used being either simulated or low-dimensional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Teti et al (69) employed sparse coding with lateral inhibition in simulations of neuronal activation in visual cortex. More recently, Młynarski et al (41) presented a probabilistic framework combining normative priors with statistical inference and demonstrated the usefulness of this approach for the analysis of diverse neuroscientific datasets. However, their work was rather conceptual, with the datasets they used being either simulated or low-dimensional.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the intersection between EC and SI has long remained largely unexplored but lately shifted more into focus. In particular, Mlynarski and colleagues recently proposed a theoretical framework incorporating normative theories for statistical inference on simulated or pre-fit neural data (41). Their framework enables conducting rigorous statistical hypothesis tests of coding principles, but has not yet been applied to predicting neural responses to arbitrary stimuli with minimal assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we could obtain misleading results if the recorded network is only approximately optimal. To deal with this, recent work by one of the present authors [45] proposed a framework in which the neural network is assumed to satisfy a known optimality criterion approximately. In this work, the optimality criterion is formulated as a Bayesian prior, which serves to nudge the network towards desirable solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Combined, our results develop a framework and provide support for the role of efficient neuronal coding in behavior. The efficient coding hypothesis has emerged as one of the leading principles in computational neuroscience that has shaped our understanding of neuronal coding, architecture and evolution 1,22,[76][77][78] . Prior research found that human behavior follows principles of efficiency 19,24 .…”
Section: The Missing Link Between Efficient Coding and Behaviormentioning
confidence: 99%
“…The efficient coding hypothesis has been formally implemented through normative models of brain function 3,4,[20][21][22][23] . These models assess whether and how neuronal adaptation shapes sensory information and simulate how such adaptation might constrain behavior.…”
Section: Introductionmentioning
confidence: 99%